REST API Menggunakan NodeJS pada Aplikasi Transaksi Jasa Elektronik Berbasis Android - Irfan Kurniawan; Humaira; Fazrol Rozi (SOTVI - Society of Visual Informatics, 2020)
Previously, sales and service offerings were only carried out directly, which of course made consumers feel less interested, because they had to exhaust themselves to go to places of people who opened services. From this problem, a system regarding service transactions was developed based on the Application programming Interface (API) as the backend and implemented on the mobile android as the frontend. In this final project, produce an API-based system with REST architecture in terms of backend to facilitate the service transaction process and apply it to an android application as a user interface.